EFFECT OF ROSELLE (HIBISCUS SABDARIFFA) ON CHANGES IN HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA TAKING IRON SUPPLEMENT - Rif’atun Nisa; Ariawan Soejoenoes; Sri Wahyuni (Belitung Raya Foundation, Indonesia, 2017)
Background: Anemia during pregnancy is one of the most common disorders in pregnant women in Indonesia. The Government has made efforts to overcome this problem, however, the rate of anemic mothers remains high. Rosella (Hibiscus Sabdariffa) is considered able to increase the hemoglobin levels in pregnant mothers. Objective: To analyze the effect of Rosella flower extract (Hibiscus Sabdariffa) on the increase of Hemoglobin level in pregnant women with anemia receiving Fe tablet. Methods: This study was a quasi-experiment with pretest-posttest control group design conducted in November - December 2016 in the working area of Tlogosari Wetan Community Health Center. Forty-two participants were selected using accidental sampling, which 21 assigned in the experiment and control group. All samples were pregnant women in the second trimester suffering from anemia and receiving iron tablets. Hemoglobin levels were measured using hematology analyzer in laboratory. Independent t-test and paired t-test were used for data analysis. Results: Paired t-test obtained p-value 0.00 (<0.05) indicated that there was an increase of hemoglobin levels in both experiment and control group. The mean increase of hemoglobin levels in the control group was 0.61 gr/dl and in the experiment group was 1.08 gr/dl. The hemoglobin levels in the experiment group were higher than the levels in the control group. Independent t-test obtained p-value 0.000 (<0.05) indicated that there was a significant difference of mean of hemoglobin levels between the control group and the treatment group. Conclusion: The consumption of rosella extract combined with Fe tablet showed a significant increase of hemoglobin levels compared with the consumption of Fe tablet alone. Therefore, it is suggested for midwife to use the result of this research as evidence practice through counseling for pregnant mother about utilization of rosella extract that can increase hemoglobin level in pregnant woman with anemia.